2006
DOI: 10.1038/sj.jid.5700252
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen- and Stress-Activated Protein Kinase 1 Is Activated in Lesional Psoriatic Epidermis and Regulates the Expression of Pro-Inflammatory Cytokines

Abstract: Mitogen- and stress-activated protein kinase 1 (MSK1) is a downstream target of both the p38 and extracellular signal-regulated kinase 1/2 (ERK1/2) mitogen-activated protein kinases (MAPKs). MSK1 stimulates transcription of different pro-inflammatory genes through activation of transcription factors. The purpose of this study was to investigate the expression and activation of MSK1 in lesional psoriatic skin and its role in cytokine production in cultured normal human keratinocytes. Western blotting revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
63
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 33 publications
(45 reference statements)
9
63
1
Order By: Relevance
“…These data may indicate that although MSK1 and PKAc are both ROS-regulated RelA kinases, their involvement in the NF-B pathway is in a stimulus-dependent manner. We note that MSK1 is known to mediate cytokine expression in psoriatic epidermis (18) and Helicobacter pylori infection (35). Our novel finding in this study is that MSK1 is activated by RSV infection via ROS and that it plays a central role in NF-B activation via RelA Ser-276 phosphorylation.…”
Section: Discussionmentioning
confidence: 49%
“…These data may indicate that although MSK1 and PKAc are both ROS-regulated RelA kinases, their involvement in the NF-B pathway is in a stimulus-dependent manner. We note that MSK1 is known to mediate cytokine expression in psoriatic epidermis (18) and Helicobacter pylori infection (35). Our novel finding in this study is that MSK1 is activated by RSV infection via ROS and that it plays a central role in NF-B activation via RelA Ser-276 phosphorylation.…”
Section: Discussionmentioning
confidence: 49%
“…Our data also represent the first demonstration that of a role for MSK1 in any neutrophil response. Whereas MSK1 is known to be controlled by both p38 MAPK and the MEK/ERK module in some cell types and also to participate in regulating their proinflammatory cytokine expression (28,36), we found that in neutrophils, MSK1 was unaffected by MEK inhibition, thereby revealing that its regulation can be cell type specific. Similarly, although RSK kinases can phosphorylate CREB1 in other cell types (37,38), we found that the RSK inhibitor, BI-D1870, had no effect on CREB1 phosphorylation in neutrophils (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Because expression of phospho-RSK1 (T573) has previously been linked to mitosis [35], RSK activation may play a role in keratinocyte proliferation. The CREB is downstream from and dependent on MSK1 and RSK1 activation and both MSK1 and CREB are expressed and highly activated in lesional psoriatic skin [36,37]. Phospho-CREB regulates the transcription of many genes like EGF, TNF-a, Cox-2 and JunB [23].…”
Section: Discussionmentioning
confidence: 99%
“…ERK1/p42 activity induces phospho-cJun (Ser243) which inhibits the transcriptional activity of c-Jun [34,41]. Phospho-c-Jun (Ser243) masks the nuclear localisation signal sequence (NLS) in the DNA binding domain of c-Jun which inhibits nuclear transport and binding of p-c-Jun (S63) and c-Jun [36]. In our experiments, pre-incubation with DMF inhibited MIF-induced phospho-c-Jun (S243) expression in the cytosol, which supported the nuclear translocation of p-c-Jun (S63) and c-Jun.…”
Section: Discussionmentioning
confidence: 99%